Globalization and Economic Growth in West Africa (1990 - 2019) - Usman, Owolabi A. (Advances in Social Sciences Research Journal, 2022)
This study investigated the impact of overall and economic globalizations on economic growth in West Africa between 1990 and 2019.Data were sourced secondarily from the World Development Indicators (WDI) and Konjunkturforshungsstelle (KOF) data base.The study employed Pooled Ordinary Least Suare (OLS) and Fixed effect OLS for data analysis.The result obtained from sPooled OLS revealed that overall globalization had significant and positive impact on economic growth in West Africa while the result from Fixed effect showed otherwise.Further,the result from Pooled OLS also showed positive and significant effect of economic globalization on economic growth while the result from the Fixed effect showed no impact of economic globalization on economic growth in West Africa.Therefore, the study recommended that Government policy should adopt overall globalization as a major factor of economic growth.Also, Government should formulate policy to encourage trade openness,Foreign Direct Investment (FDI) and capital inflows which are the major platform upon which economic globalization rested.